DETERMINATION OF INTRINSIC MOTIVATION, ORGANIZATIONAL CULTURE, AND ORGANIZATIONAL COMMUNICATION TOWARDS WORK LOYALTY WITH WORK SATISFACTION AS AN INTERVENING VARIABLE - Andriani, Deska Astri; Wibisono, Chablullah; Satriawan, Bambang; Adi, Nyoman Rasmen (International Journal of Psychosocial Rehabilitation, 2020)
Based on the background of the problems that occurred at PT. Bank Permata Batam, then researched to analyze the determination of intrinsic Motivation, Organizational Culture, and organization Communication on work loyalty through job satisfaction at PT. Bank Permata Batam. This study consists of three independent variables: intrinsic Motivation, Organizational Culture, and Organizational Communication, and work Loyalty as the dependent and intervening variables of job satisfaction. The research method used is descriptive quantitative, which explains the work motivation's work motivation, the organizational culture of work loyalty, and job satisfaction at PT. Bank Permata Batam by collecting data and testing hypotheses and providing conclusions from research results using a questionnaire. Data collection techniques for distributing questionnaires, data analysis techniques using simple regression. Respondents in this study respondents were employees of PT. Bank Permata Batam, totaling 161 people, then analyzed independent variables, mediator variables, and dependent variables using the SEM test using AMOS version 24.0. In contrast, changes in Work Loyalty are influenced by Intrinsic Motivation, Organizational Culture, and Organizational Communication by 44.6%. All populations were sampled using the census method. Validity and reliability were tested using the SPSS version, then analysis of independent variables, mediator variables, and dependent variables using the SEM test using AMOS version 24.0. From the results of research, changes in Job Satisfaction are influenced by Intrinsic Motivation, Organizational Culture, and Organizational Communication by 45.5%. In contrast, changes in Work Loyalty are influenced by Intrinsic Motivation, Organizational Culture, and Organizational Communication by 44.6%